Beyond Family Ties: Intergenerational Trauma as a Predictor of Mental Well-being Among Indonesian Youth - Anggi Mayangsari; Reny Rustyawati; Sri Juwita Kusumawardhani; Vivi Ariantika (Utan Kayu Publishing, 2026)
Intergenerational trauma has been recognized as a significant psychological factor affecting mental health outcomes across generations. This study examined the influence of intergenerational trauma and family relationship on the mental well-being of young adults in Indonesia. A total of 103 participants were recruited through convenience sampling and completed the Indonesian-adapted versions of the Historical Intergenerational Trauma Transmission Questionnaire (HITT-Q), the General Functioning of Family scale, and the Warwick-Edinburgh Mental Well-being Scale (WEMWBS). Results from multiple linear regression analysis indicated that the overall regression model was statistically significant , F(2, 100) = 29.36, p < .001. However, only intergenerational trauma had a significant independent effect (B = –0.18, p < .001), suggesting that higher levels of inherited trauma were associated with lower mental wellbeing. Family functioning did not show a significant independent effect (B = 0.05, p = .739). Descriptive analysis also revealed that 77.7% of participants were classified as having low levels of mental well-being . These findings underscore the importance of addressing intergenerational trauma in efforts to improve mental health outcomes, especially mental wellbeing among young adults in Indonesia. Abstrak: Trauma antar generasi telah diakui sebagai faktor psikologis signifikan yang memengaruhi hasil kesehatan mental lintas generasi. Studi ini meneliti pengaruh trauma antar generasi dan hubungan keluarga terhadap kesejahteraan mental kaum muda di Indonesia. Sebanyak 103 partisipan direkrut melalui pengambilan sampel acak dan menyelesaikan versi adaptasi bahasa Indonesia dari Historical Intergenerational Trauma Transmission Questionnaire (HITT-Q), the General Functioning of Family scale, and the Warwick-Edinburgh Mental Well-being Scale (WEMWBS). Hasil dari analisis regresi linier berganda menunjukkan bahwa model regresi secara keseluruhan signifikan secara statistik , F(2, 100) = 29,36, p < 0,001. Namun, hanya trauma antar generasi yang memiliki efek independen signifikan (B = –0,18, p < 0,001), menunjukkan bahwa tingkat trauma yang diwariskan lebih tinggi dikaitkan dengan kesejahteraan mental yang lebih rendah. Fungsi keluarga tidak menunjukkan efek independen yang signifikan (B = 0,05, p = 0,739). Analisis deskriptif juga mengungkapkan bahwa 77,7% peserta dikategorikan memiliki tingkat kesejahteraan mental yang rendah . Temuan ini menggarisbawahi pentingnya mengatasi trauma antar generasi dalam upaya meningkatkan hasil kesehatan mental, terutama kesejahteraan mental di kalangan dewasa muda di Indonesia.